Stress-inducing or performance-enhancing? Safety measure or cause of mistrust? The paradox of digital surveillance in the workplace - Elisa Giacosa; Gazi Mahabubul Alam; Francesca Culasso; Edoardo Crocco (Journal of Innovation & Knowledge (JIK), 2023)
The advent of digital technology has inevitably changed the modern workplace. While digital transformation has been beneficial for companies in terms of added productivity and efficiency-it has simultaneously unveiled several grey areas that are worth investigating, such as the topics of digital surveillance and its implications for technostress, performance and trust. While academic research has kept pace with rising industry interest, especially in the wake of the COVID-19 pandemic, the literature on digital surveillance has only recently gained traction compared to the rest of the digital transformation literature. In an effort to synthesize extant academic production on digital surveillance and provide guidance for future research directions on the topic, the present study utilizes a critical systematic literature review (SLR) to analyze literature published on the topic of digital surveillance. Making use of a clearly defined search protocol, we examined the content of 57 distinct studies. Subsequently, three main thematic areas of research are identified through the use of content analysis: the implications of digital surveillance on technostress, the correlation between digital surveillance and performance, and the ways in which digital surveillance can affect trust and acceptance. Additionally, several gaps are identified in the extant literature, and subsequent paths for further research are proposed. The study offers both theoretical and practical implications. From a theoretical perspective, the present SLR contributes to the literature stream of digital surveillance by critically reviewing and synthesizing extant scientific production and compiling a research agenda for future studies. From a practical perspective, this study provides valuable insights to support current efforts by practitioners seeking to effectively implement digital surveillance in the workplace.
Keywords: L1; M0; M1; M5; O2; O3; 650; Digital transformation; Monitoring; Surveillance; Systematic review; Workplace